KARAKTERISTIK DAKWAH KHULAFA AL-RASYIDIN - Muhammad Patri Arifin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
After the Prophet Muhammad passed away, Islamic propagation was carried out the Prophet’s companions, such as Abu Bakr, Umar, Uthman and Ali, known as Khulafa’ Rashidin (rightly guided caliphs). Their mission of da’wah was never deviated from the teachings of the Prophet, but carried out with different practices. Abu Bakr, for example, paid special attention to the spread of true way of life. Because of his efforts, most Arabs converted to Islam. After Abu Bakr’s caliphate, Umar managed Islamic government and effective administration. At Uthman’s period, he extinguished rebellion that occurred in some areas, and expanded the reign of Islam that halted in the caliphate of Umar. In addition, Uthman’s spectacular effort is the collection and writing of the Quran, later known as the Ottoman Manuscripts. In his period, Ali applied the principle of equality among Muslims, while a political aspect, he was very decisive in supervising his staffs and officials (local authorities).